IMPLEMENTASI FUNGSI PENGAWASAN DPRD DALAM KEBIJAKAN PEMERINTAH DAERAH DI KOTA PALEMBANG - Husni Holqiah; Yollanda Apriapamela; Riska Sakinah; Yuyun Yuliana (CV The Journal Publishing, 2020)
The main function of the DPRD is to control the running of the government in the regions, while with regard to the legislative function, the position of the DPRD is not a dominant actor. The dominant power holder in the legislative field is the Governor or Regent/Mayor. Even in Law No.23 / 2014, Governors and Regents / Mayors are required to submit a draft Regional Regulation and stipulate it as a Regional Regulation with the approval of the DPRD. This means that the DPRD only acts as a controller that can approve or even reject at all or approve certain changes. However, many facts show that there are still many Parliament members who do not have comprehensive capabilities in carrying out supervisory functions which result in not being able to function properly. This phenomenon also occurs in the Palembang City Parliament where there are still many Parliament members who do not know how to carry out the supervisory function which is one of their main tasks. One of them is at least the Palembang City DPRD members who attended the plenary session which was attended directly by the Mayor of Palembang, which we will discuss in this study. The purpose of this study is to describe the Implementation of the DPRD Supervision function in the Regional Government's policy and at the same time to find out the factors that influence in carrying out the supervisory function so it expected to find a solution to handle it in.